2011
DOI: 10.1371/journal.pone.0026647
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dysregulates Corticotropin-Releasing-Hormone (CRH) Promoter Activity by Interfering with the Negative Glucocorticoid Response Element (nGRE)

Abstract: EtOH exposure in male rats increases corticotropin-releasing hormone (CRH) mRNA in the paraventricular nucleus of the hypothalamus (PVN), a brain region responsible for coordinating stress and anxiety responses. In this study we identified the molecular mechanisms involved in mediating these effects by examining the direct effects of EtOH on CRH promoter activity in a neuronal cell line derived from the PVN (IVB). In addition, we investigated the potential interactions of EtOH and glucocorticoids on the CRH pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
(32 reference statements)
3
16
0
Order By: Relevance
“…This is consistent with our previous observations in vivo (Przybycien-Szymanska et al, 2011b), and in vitro , in which we observed that alcohol inhibits GR binding to the CRF promoter in IVB cells, which are derived from rat PVN (Przybycien-Szymanska et al, 2011a). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with our previous observations in vivo (Przybycien-Szymanska et al, 2011b), and in vitro , in which we observed that alcohol inhibits GR binding to the CRF promoter in IVB cells, which are derived from rat PVN (Przybycien-Szymanska et al, 2011a). …”
Section: Discussionsupporting
confidence: 93%
“…Further behavioral studies are required to determine whether the observed differences in the amount of time spent in the intersection of the maze between rats exposed to alcohol as adolescents versus controls on repeated trials in the EPM are due to changes in learning abilities or the emotional state of the animal.To better examine the causal effects of adolescent binge alcohol consumption on the HPA axis and anxiety behavior, many different animal studies have been conducted with varying results. Our lab and others have established animal models demonstrating that adolescent binge alcohol exposure does indeed induce long-term effects on the regulation of the HPA axis (Allen et al, 2011; Przybycien-Szymanska et al, 2011a). However, observations that adolescent binge alcohol exposure induces changes in anxiety-like behaviors seem to vary based on the specific animal model used.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand the molecular mechanism behind the harmful effects of ethanol gene expression profiling. Several investigations have already been reported which tried to unveil the mechanisms of ethanol-induced gene expression alteration in different aspects [17][18][19][20][21]. But the alcohol-regulated genes and their associated biological pathways have not yet been completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…To efficiently identify CRH-expressing neurons in rat PVN, we constructed a viral plasmid containing rat Crh promoter [44] and eGFP and integrated this plasmid into an adeno-associated virus (AAV) vector construct. The full-length promoter fragment (−2125/+94) was subcloned into the AAV vector expression cassette by using short regulatory elements (woodchuck post regulatory element 2 [WPRE2] and short synthetic polyadenylation [SpA]).…”
Section: Methodsmentioning
confidence: 99%